THE EFFECTIVENESS OF BOOKTRACK FOR TEACHING READING COMPREHENSION - Oktabriyanti, Sita; Hartono, Rudi; Areni, Galuh K.D. (ELT Forum: Journal of English Language Teaching, 2018)
The aim of this study is to find out the effectiveness of Booktrack in teaching reading comprehension on the tenth grade students of a senior high school in Semarang. In order to achieve the objective of this research, the writer designed a quasi-experimental study. The subject of this study was 64 students of the tenth grade of a senior high school in Semarang; 32 students acted as the experimental group to be taught reading comprehension by using Booktrack App and the other 32 students as the control group to be taught reading comprehension by using regular medium. The results of the study showed that the score of experimental group was higher than control group. Based on the results, it can be concluded that Booktrack App is effective as a medium in teaching reading comprehension.